World dairy system sustainability: a milk quality perspective - Priyashantha, Hasitha (Frontiers in Sustainable Resource Management, 2025)
The dairy industry is a crucial component of global food systems, providing essential nutrition and economic benefits to billions of livelihoods worldwide. Amidst growing challenges, the potential of milk quality to transform sustainability efforts in the dairy processing industry and milk production systems is increasingly evident. This review discusses and investigates milk quality as a key driver for achieving environmental efficiency, reducing waste, and enhancing processing outcomes, all while safeguarding consumer health and delivering superior nutritional value. The use of improved technologies such as precision farming, automatic milking systems, and genetic selection are explored as transformative tools to enhance milk quality and optimize resource use to uplift sustainability within the industry. The dairy industry must reduce emissions associated with milk processing, while the dairy farming sector must address emissions at the raw milk production stage. Case studies included in this article illustrate successful models integrating milk quality into sustainability frameworks, emphasizing regional adaptations. Future research must prioritize to maintain or uplift the milk quality through development of climate-resilient dairy systems, innovations in circular economy practices, and scalable solutions for low- and middle-income regions. Integrating milk quality into sustainability initiatives ensures balanced economic, environmental, and social benefits, fostering resilience in the global dairy sector.